Intussusception of the small intestine loop into the gastric lumen through gastroenteroanastomosis after pancreaticoduodenectomy: A clinical case - P. V. Markov; S. О. Zagagov; O. R. Arutyunov; M. V. Kornaeva (Кубанский научный медицинский вестник, 2024)
Background. Intussusception of the small intestine loop through gastroenteroanastomosis is considered a rare but potentially dangerous complication that can occur after gastroenteroanastomosis surgery. This complication is extremely seldom associated with pancreaticoduodenectomy.Case description. A 44-year male patient underwent pancreaticoduodenectomy for common bile duct cancer on 07.10.2019, followed by adjuvant chemotherapy. On April 14, 2021 he was admitted for the next course of chemotherapy and complained of pain in the epigastric region and nausea, that appeared a few days ago, thus, he was appointed an urgent additional examination. Gastroscopy revealed a loop of small intestine, prolapsing into the lumen of the gastric remnant through the gastroenteroanastomosis. The fixed loop of intestine precluded endoscopic disinvagination from being performed. Computed tomography confirmed intussusception of the small intestine loop through gastroenteroanastomosis. The patient underwent emergency surgery. Laparotomy revealed a 40 cm intussusception of the small intestine loop through gastroenteroanastomosis into the gastric remnant. The intestine loop was accurately disinvaginated and proved to be viable. The intestine loop was additionally fixed to prevent re-intussusception. After the complication-free postoperative period, the patient was discharged on day 6. The follow-up examination in 6 months revealed no signs of intussusception recurrence according to computed tomography. The paper reviewed the internationally published cases of jejunogastric intussusception after pancreaticoduodenectomys.Conclusion. Jejunogastric intussusception refers to an extremely rare complication after a previously performed pancreaticoduodenectomy. A risk of the complications is to be recognized, since their timely diagnosis and surgical treatment enable successful outcome to be achieved.